Phase-change temperature-control flame-retardant current collector and preparation method and application thereof

By using porous copper film to fill phase change materials and flame retardant current collectors in lithium batteries, the risks of high temperature response hysteresis and thermal runaway spontaneous combustion in lithium batteries are solved, and efficient thermal management and safety protection are achieved.

CN119560568AActive Publication Date: 2025-03-04HUAZHONG UNIV OF SCI & TECH

Patent Information

Application Number
CN202411752370.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-04
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing lithium battery thermal management system cannot effectively solve the risks of high-temperature response hysteresis and thermal runaway spontaneous combustion in the battery, and the low space utilization and thermal conductivity of organic phase change materials have increased the thermal safety hazards of the battery.

Method used

A three-dimensional interconnected porous copper film is used as the substrate of the temperature-controlled flame retardant layer, filled with phase change materials and flame retardant agents, forming a phase change temperature-controlled flame retardant current collector of the conductive coating and the temperature-controlled flame retardant layer, achieving efficient heat absorption inside the battery and flame retardant protection when heat runaway is achieved.

Benefits of technology

This technology effectively improves the thermal stability and safety of lithium batteries, and significantly reduces the risk of thermal runaway by efficiently absorbing internal heat and releasing flame retardant when thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560568A_ABST
    Figure CN119560568A_ABST
Patent Text Reader

Abstract

The invention provides a phase-change temperature-control flame-retardant current collector and a preparation method and application thereof. The current collector comprises a conductive coating and a temperature-control flame-retardant layer, the conductive coating comprises a first conductive coating and a second conductive coating and is used for loading an active material and packaging the temperature-control flame-retardant layer, and the temperature-control flame-retardant layer is arranged between the first conductive coating and the second conductive coating; the temperature-control flame-retardant layer takes a porous copper film as a matrix, and the porous copper film is filled with a phase-change material and a flame retardant. According to the phase-change temperature-control flame-retardant current collector provided by the invention, the latent heat of the volume ratio is greater than 100J / cm < 3 >, the heat conductivity is greater than 150W / m.K, and the thickness is 10-50 microns, so that the problems of low space utilization rate, low loading capacity and low heat conductivity of a phase-change material in a current temperature-adjusting diaphragm and a temperature-adjusting electrode are well solved. In addition, the battery internal temperature control assembly has the characteristics of simple structure, high integration level and low cost, and the actual application requirement of the battery internal temperature control assembly is well met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of thermal management of lithium batteries, and in particular to a phase-change temperature-controlled flame-retardant current collector and a preparation method and application thereof. Background Art

[0002] With the rapid development of lithium-ion power and energy storage industries, the pursuit of high specific energy density and high charge and discharge rate has become an urgent need. However, the heat generation problem during battery operation cannot be ignored. Once the battery temperature exceeds its operating temperature threshold, it will seriously affect the cycle life and increase the risk of thermal runaway and spontaneous combustion. Therefore, how to reliably control the temperature of lithium-ion batteries within an appropriate range is a major practical problem.

[0003] Currently, battery thermal management systems perform temperature control based on thermocouple readings on the battery surface and remove heat from the surface through a cooling medium (such as air, coolant, or phase change material). With the development of internal battery temperature measurement technology, people are increasingly aware that batteries will produce large temperature gradients when operating at high rates, which is due to the rapid heat generation and the low thermal conductivity of battery materials. Obviously, external heat dissipation can reduce the average temperature of the battery module to a certain extent, but it cannot directly solve the problems of heat accumulation and uneven temperature distribution inside the battery cell.

[0004] Combining organic phase change materials with internal components of the battery is a new internal temperature control method. Phase change materials spontaneously respond to high temperatures and absorb heat through phase conversion. This process is passive and efficient. Patent CN104201321A proposes that a diaphragm with phase change thermostat function is prepared by melt mixing and extrusion molding of phase change microcapsules and polyethylene. In addition, patent CN111430709A also combines phase change microcapsules with electrode layers to prepare phase change temperature control electrodes. However, the porosity of the diaphragm and electrode layer is generally above 50% for absorbing electrolyte (high porosity is to ensure the rapid transmission of lithium ions), coupled with the inherent materials of the diaphragm and electrode layer (such as polymer matrix, active material, conductive agent and binder) and the space occupied by the microcapsule shell, which leads to the problem of low space utilization and low load of phase change materials in such technical solutions. In addition, the low thermal conductivity of organic phase change materials will limit their heat absorption efficiency. Under the trend of high integration and fast charging of batteries, it is necessary to develop high thermal conductivity internal temperature control components that load more phase change materials. In addition to the difficulty in preparing internal temperature control components, since organic phase change materials have certain fire hazards and can easily "add fuel to the fire" when thermal runaway occurs in lithium-ion batteries, built-in phase change materials may aggravate the hazards of thermal runaway of batteries.

[0005] Therefore, there is an urgent need to develop a new internal temperature control component for lithium batteries to solve the problem of the delayed response of the external thermal management system to the high temperature inside the battery, so that it can provide effective protection when the lithium battery is overheated and prevent thermal runaway and fire accidents. Summary of the invention

[0006] In view of this, the present invention proposes a phase-change temperature-controlled flame-retardant current collector and its preparation method and application. The current collector can quickly absorb the internal heat generated during the operation of the battery through the encapsulated phase-change material, and at the same time, when the battery has thermal runaway, it can release the encapsulated flame retardant in time, thereby reducing the harm caused by thermal runaway.

[0007] In the first aspect, the present invention provides a phase-change temperature-controlled flame-retardant current collector, comprising a conductive coating and a temperature-controlled flame-retardant layer, wherein the conductive coating comprises a first conductive coating and a second conductive coating, wherein the conductive coating is used to load active materials and encapsulate the temperature-controlled flame-retardant layer, and the temperature-controlled flame-retardant layer is arranged between the first conductive coating and the second conductive coating; the temperature-controlled flame-retardant layer is based on a porous copper film, and the porous copper film is filled with a phase change material and a flame retardant.

[0008] By adopting the above technical solution, the present invention uses a three-dimensionally interconnected porous copper film as the matrix of the temperature control flame retardant layer, and fills the phase change material and flame retardant in the porous copper film, so that when the battery is overheated during operation, the phase change material in the temperature control flame retardant layer can quickly absorb excess heat to ensure that the battery is maintained within a suitable operating temperature range. In addition, if the battery has thermal runaway, the conductive coating will crack under the action of thermal shock, prompting the flame retardant in the temperature control flame retardant layer to be released, effectively reducing the risk of thermal runaway, while avoiding secondary dangers caused by phase change materials.

[0009] Furthermore, the material of the first conductive coating and / or the second conductive coating is selected from one of aluminum, copper, silver, nickel or platinum; and the thickness of any of the conductive coatings is 1 to 5 μm.

[0010] Furthermore, the temperature-controlling flame-retardant layer has a thickness of 10 to 50 μm.

[0011] Furthermore, the porous copper film has a porosity of 40-80%, an average pore size of 0.5-2.0 μm, and a thickness of 10-50 μm.

[0012] Furthermore, the organic phase change material is one or more of paraffin, n-docosane, tetracosane, tetradecanol, hexadecanol, octadecyl alcohol, lauric acid, tetradecanoic acid, hexadecanoic acid and stearic acid; the flame retardant is one or more of trimethyl phosphate, triethyl phosphate and triphenyl phosphate.

[0013] Furthermore, the mass ratio of the phase change material to the flame retardant is 80:20 to 97:3.

[0014] In a second aspect, the present invention also relates to a method for preparing the above-mentioned phase-change temperature-controlled flame-retardant current collector, comprising the following steps:

[0015] S1: Pre-preparation of porous copper film: placing a copper alloy foil in an acidic aqueous solution, heating and stirring, taking out the copper alloy foil after no bubbles are generated on the surface, washing, and drying to obtain a pre-treated porous copper film;

[0016] S2: adjusting the pores of the porous copper film: using the porous copper film in step S1 as an anode, the phosphor copper sheet as a cathode, and a mixed aqueous solution of sulfuric acid and copper sulfate as an electrolyte, connecting a constant current power supply to electrochemically corrode the porous copper film; after the treatment is completed, washing and drying to obtain a secondary treated porous copper film;

[0017] S3: Preparation of temperature-controlled flame-retardant layer: heating and stirring the phase change material and the flame retardant to form a liquid mixture; immersing the porous copper foil in step S2 in the liquid mixture and placing it in a constant temperature vacuum environment to obtain a porous copper film adsorbed with the phase change material and the flame retardant, placing it between polyethylene filter membranes, hot pressing, and cooling it at room temperature to obtain a temperature-controlled flame-retardant layer;

[0018] S4: Preparation of phase-change temperature-controlled flame-retardant current collector: A conductive coating is deposited on both sides of the temperature-controlled flame-retardant layer in step S3 to prepare a phase-change temperature-controlled flame-retardant current collector.

[0019] On the basis of the above technical solution, preferably, in step S1 and / or step S2, the cleaning method is: cleaning with deionized water and anhydrous ethanol at least three times respectively.

[0020] On the basis of the above technical solution, preferably, in step S4, the deposition method is selected from one of evaporation coating, magnetron sputtering, electroplating or chemical plating.

[0021] On the basis of the above technical solution, in step S3, the purpose of the hot pressing treatment is to remove the residual liquid on the surface of the porous copper film.

[0022] In step S1 of the present invention, it includes:

[0023] Furthermore, the copper alloy is one of copper-zinc alloy (brass), copper-nickel alloy (white copper), copper-zinc-nickel alloy (nickel silver), copper-tin alloy (bronze) and copper-manganese alloy (manganese-copper); in the copper alloy, the mass fraction of copper is 30 to 80%.

[0024] Furthermore, the thickness of the foil is 10-50 μm.

[0025] Furthermore, the heating and stirring temperature is 50-90° C., and the stirring speed is 200-600 rpm.

[0026] Furthermore, the acid used in the acidic aqueous solution is one or more of sulfuric acid, hydrochloric acid, phosphoric acid and acetic acid, and the concentration is 0.1-1.0 mol / L.

[0027] In step S2 of the present invention, it includes:

[0028] Furthermore, the reaction temperature of the chemical etching treatment is 50-90° C., and the stirring speed is 200-600 rpm.

[0029] Furthermore, the electrolyte used in the electrochemical corrosion treatment has a sulfuric acid concentration of 0.1 to 2.0 mol / L and a copper sulfate concentration of 0.1 to 0.6 mol / L.

[0030] Furthermore, the electrochemical corrosion treatment conditions are: the current density is 0.5-2.0 mA / cm 2 , lasting for 0.5 to 6 hours.

[0031] In step S3 of the present invention, it includes:

[0032] Furthermore, the heating and stirring temperature is 40-90° C., the stirring speed is 200-600 rpm, and the duration is 0.5-4 h.

[0033] Furthermore, the constant temperature vacuum conditions are: vacuum degree -0.6 to -0.8 MPa, temperature 50 to 80°C, and duration 3 to 20 minutes.

[0034] Furthermore, the hot pressing conditions are: pressure 0.02-0.5 MPa, temperature 50-90° C., and duration 1-5 min.

[0035] In the third aspect, the present invention also relates to the application of the above-mentioned phase-change temperature-controlled flame-retardant current collector in lithium batteries, which is specifically manifested in that the phase-change temperature-controlled flame-retardant current collector integrates phase-change materials and flame retardants to achieve efficient thermal management and safety protection of lithium batteries under overheating conditions. This design not only improves the thermal stability of lithium batteries, but also enhances their safety under extreme conditions.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1. The phase-change temperature-controlled flame-retardant current collector prepared by the present invention can absorb heat in situ inside the battery and respond quickly to the heat accumulated inside the battery. In addition, the addition of flame retardants solves the flammability risk of organic phase change materials and improves the thermal safety of lithium batteries.

[0038] 2. The volume specific latent heat of the phase change temperature control flame retardant current collector prepared by the present invention is greater than 100 J / cm 3 The thermal conductivity is greater than 150W / m·K, while the thermal conductivity of most organic phase change materials is only 0.2W / m·K. This is mainly due to the fact that the thermal conductivity network composed of the metal conductive coating and the porous copper matrix greatly reduces the thermal resistance, and the porosity of the selected porous copper matrix is ​​distributed between 40% and 80%, which significantly improves the space utilization of the phase change material and effectively increases the load of the phase change material.

[0039] 3. The phase-change temperature-controlled flame-retardant current collector prepared by the present invention has a good encapsulation effect on the phase-change material. The double treatment of chemical corrosion and electrochemical corrosion makes the pore size of the porous copper film between 0.5 and 2.0 μm. In comparison, the pore size of commercial copper foam exceeds 150 μm. The small pore size significantly improves the capillary adsorption force of the phase-change material. In addition, the conductive coating further prevents the leakage of the phase-change material.

[0040] 4. The phase-change temperature-controlled flame-retardant current collector prepared by the present invention has a thickness of 10 to 50 μm, and therefore has little negative impact on the battery energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 1 is a schematic diagram of the structure of the phase-change temperature-controlled flame-retardant current collector of the present invention; in the figure, 1 is a conductive coating; 11 is a first conductive coating; 12 is a second conductive coating; 2 is a temperature-controlled flame-retardant layer;

[0043] Figure 2 is a scanning electron microscope image of the phase-change temperature-controlled flame-retardant current collector obtained in Example 1 of the present invention;

[0044] Figure 3 is a differential scanning calorimetry curve of the phase-change temperature-controlled flame-retardant current collector obtained in Example 1 of the present invention;

[0045] Figure 4 This is a scanning electron microscope image of the porous copper film in Comparative Example 1 of the present invention;

[0046] Figure 5 This is a scanning electron microscope image of the porous copper film in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0047] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] like Figure 1 As shown, the present invention provides a phase change temperature control flame retardant current collector, including a conductive coating and a temperature control flame retardant layer, wherein the conductive coating includes a first conductive coating and a second conductive coating, the conductive coating is used to load active materials and encapsulate the temperature control flame retardant layer, and the temperature control flame retardant layer is arranged between the first conductive coating and the second conductive coating; the temperature control flame retardant layer is based on a porous copper film, and the porous copper film is filled with phase change material and flame retardant.

[0049] The working principle of the phase change temperature-controlled flame-retardant current collector is as follows: the phase change material absorbs accumulated heat when the lithium battery is working normally to maintain a stable temperature; when the temperature of the lithium battery abnormally rises to a critical point, the encapsulated flame retardant is activated and released, quickly suppressing combustion, thereby effectively reducing the hazards of thermal runaway and ensuring the safety of the lithium battery.

[0050] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The sources of materials mainly involved in the examples are all conventional commercial products.

[0051] Example 1

[0052] The phase-change temperature-controlled flame-retardant current collector provided in this embodiment is prepared by the following steps:

[0053] A 10cm*10cm*20μm H65 brass foil (the mass fractions of copper and zinc are 64% and 36%, respectively) was placed in a 1L acidic aqueous solution for chemical corrosion treatment. The ratio of the acidic aqueous solution was 1.0MH2SO4+1.0M H3PO4. The reaction was carried out at 80℃ and 200rpm for 24h. After the reaction was completed, it was washed with deionized water and anhydrous ethanol three times each, and the porous copper film was obtained after drying.

[0054] The porous copper film treated initially was used as the anode, and an electrolytic cell was formed with a phosphor copper sheet cathode and an aqueous electrolyte to perform electrolytic corrosion treatment on the porous copper film. The ratio of the aqueous electrolyte was 0.5M CuSO4+1.0MH2SO4, and the current density of the electrochemical corrosion was 1.0mA / cm 2 , the corrosion time is 4h. After completion, it is washed with deionized water and anhydrous ethanol three times respectively, and the secondary treated porous copper film is obtained after drying;

[0055] Paraffin wax and triphenyl phosphate with a mass ratio of 95:5 were mixed at 60°C and 200 rpm for 4 hours, and the secondary treated porous copper film was immersed in the molten mixture and placed at 70°C and a vacuum of -0.6MPa for 3 minutes. The porous copper film filled with phase change material and flame retardant was taken out, placed in two polyethylene filter membranes, and hot pressed to remove the residual liquid on the surface. The hot pressing conditions were a pressure of 0.05MPa, a temperature of 70°C, and a duration of 3 minutes. After completion, it was cooled at room temperature to obtain a temperature-controlled flame retardant layer;

[0056] The temperature-controlled flame-retardant layer is used as the cathode, and the phosphor copper sheet anode and commercial copper plating solution form an electrolytic cell to perform surface electroplating on the flame-retardant phase-change composite film. The current density of the surface electroplating treatment is 2.0 mA / cm 2 The duration is 1 hour, and the thickness of the electroplated layer is 2 μm. After completion, it is washed with deionized water and anhydrous ethanol three times each, and the phase change temperature control flame retardant current collector is obtained after drying.

[0057] The phase-change temperature-controlled flame-retardant current collector prepared in Example 1 was observed by electron microscope, and the following results were obtained: Figure 2 The scanning electron microscope image shown is Figure 2 It can be seen that the mixture of phase change material and flame retardant completely fills the pores of the porous copper film, and at the same time the electroplated copper layer is tightly combined with the temperature-controlled flame retardant layer, achieving good encapsulation of the phase change material and flame retardant.

[0058] The phase-change temperature-controlled flame-retardant current collector prepared in Example 1 was subjected to differential scanning calorimetry, and the following results were obtained: Figure 3 The differential scanning calorimetry curve shown in Figure 3 It can be seen that the narrow and sharp peak represents the heat absorption and heat storage characteristics of the encapsulated phase change material, and the high volumetric latent heat of the phase change temperature-controlled flame-retardant current collector is due to the high phase change material filling rate.

[0059] Example 2

[0060] The phase-change temperature-controlled flame-retardant current collector provided in this embodiment is prepared by the following steps:

[0061] A 10cm*10cm*50μm H65 brass foil (the mass fractions of copper and zinc are 64% and 36%, respectively) was placed in a 1L acidic aqueous solution for chemical corrosion treatment. The ratio of the acidic aqueous solution was 1.0MH2SO4+1.0M H3PO4. The reaction was carried out at 90℃ and 400rpm for 72h. After the reaction was completed, it was washed with deionized water and anhydrous ethanol three times each, and the porous copper film was obtained after drying.

[0062] The porous copper film treated initially was used as the anode, and an electrolytic cell was formed with a phosphor copper sheet cathode and an aqueous electrolyte to perform electrolytic corrosion treatment on the porous copper film. The ratio of the aqueous electrolyte was 0.5M CuSO4+1.0MH2SO4, and the current density of the electrochemical corrosion was 2.0mA / cm 2 , the corrosion time is 6h. After completion, it is washed with deionized water and anhydrous ethanol three times respectively, and the secondary treated porous copper film is obtained after drying;

[0063] Paraffin wax and triphenyl phosphate with a mass ratio of 95:5 were mixed at 60°C and 200 rpm for 4 hours, and the secondary treated porous copper film was immersed in the molten mixture and placed at 70°C and a vacuum of -0.8MPa for 5 minutes. The porous copper film filled with phase change material and flame retardant was taken out, placed in two polyethylene filter membranes, and hot pressed to remove the residual liquid on the surface. The hot pressing conditions were a pressure of 0.5MPa, a temperature of 70°C, and a duration of 3 minutes. After completion, it was cooled at room temperature to obtain a temperature-controlled flame retardant layer;

[0064] The temperature-controlled flame-retardant layer is used as the cathode, and the phosphor copper sheet anode and commercial copper plating solution form an electrolytic cell to perform surface electroplating on the flame-retardant phase-change composite film. The current density of the surface electroplating treatment is 2.0 mA / cm 2 The duration is 1.5 hours, and the thickness of the electroplated layer is 3 μm. After completion, it is washed three times with deionized water and anhydrous ethanol respectively, and the phase change temperature control flame retardant current collector is obtained after drying.

[0065] Example 3

[0066] The phase-change temperature-controlled flame-retardant current collector provided in this embodiment is prepared by the following steps:

[0067] A 10cm*10cm*30μm B45 white copper foil (the mass fractions of copper and nickel are 55% and 45% respectively) was placed in 1L of acidic aqueous solution for chemical corrosion treatment. The ratio of the acidic aqueous solution was 1.0MH2SO4+1.0M H3PO4. The reaction was carried out at 80℃ and 200rpm for 48h. After the reaction was completed, it was washed with deionized water and anhydrous ethanol three times each, and the porous copper film was obtained after drying.

[0068] The porous copper film treated initially was used as the anode, and an electrolytic cell was formed with a phosphor copper sheet cathode and an aqueous electrolyte to perform electrolytic corrosion treatment on the porous copper film. The ratio of the aqueous electrolyte was 0.5M CuSO4+1.0MH2SO4, and the current density of the electrochemical corrosion was 1.5mA / cm 2 , the corrosion time is 3h. After completion, it is washed with deionized water and anhydrous ethanol three times respectively, and the secondary treated porous copper film is obtained after drying;

[0069] Paraffin wax and triphenyl phosphate with a mass ratio of 97:3 were mixed at 60°C and 200 rpm for 1 hour, and the secondary treated porous copper film was immersed in the molten mixture and placed at 70°C and a vacuum of -0.8MPa for 4 minutes. The porous copper film filled with phase change material and flame retardant was taken out, placed in two polyethylene filter membranes, and hot pressed to remove the residual liquid on the surface. The hot pressing conditions were a pressure of 0.5MPa, a temperature of 70°C, and a duration of 3 minutes. After completion, it was cooled at room temperature to obtain a temperature-controlled flame retardant layer;

[0070] The temperature-controlled flame-retardant layer is used as the cathode, and the phosphor copper sheet anode and commercial copper plating solution form an electrolytic cell to perform surface electroplating on the flame-retardant phase-change composite film. The current density of the surface electroplating treatment is 2.0 mA / cm 2 The duration is 1 hour, and the thickness of the electroplated layer is 2 μm. After completion, it is washed with deionized water and anhydrous ethanol three times each, and the phase change temperature control flame retardant current collector is obtained after drying.

[0071] Example 4

[0072] The phase-change temperature-controlled flame-retardant current collector provided in this embodiment is prepared by the following steps:

[0073] A 10cm*10cm*20μm BZn18-26 nickel silver foil (the mass fractions of copper, zinc, and nickel are 56%, 26%, and 18%, respectively) was placed in a 1L acidic aqueous solution for chemical corrosion treatment. The ratio of the acidic aqueous solution was 1.0M H2SO4+1.0M HCl+1.0M H3PO4. The reaction was carried out at 70°C and 200rpm for 24h. After the reaction was completed, it was washed with deionized water and anhydrous ethanol three times each, and the porous copper film was obtained after drying.

[0074] The porous copper film treated initially was used as the anode, and an electrolytic cell was formed with a phosphor copper sheet cathode and an aqueous electrolyte to perform electrolytic corrosion treatment on the porous copper film. The ratio of the aqueous electrolyte was 0.5M CuSO4+1.0MH2SO4, and the current density of the electrochemical corrosion was 2.0mA / cm 2 , the corrosion time is 2h. After completion, it is washed with deionized water and anhydrous ethanol three times respectively, and the secondary treated porous copper film is obtained after drying;

[0075] Paraffin wax and triphenyl phosphate with a mass ratio of 85:15 were mixed at 60°C and 600 rpm for 4 hours, and the secondary treated porous copper film was immersed in the molten mixture and placed at 70°C and a vacuum of -0.6MPa for 3 minutes. The porous copper film filled with phase change material and flame retardant was taken out, placed in two polyethylene filter membranes, and hot pressed to remove the residual liquid on the surface. The hot pressing conditions were a pressure of 0.1MPa, a temperature of 70°C, and a duration of 3 minutes. After completion, it was cooled at room temperature to obtain a temperature-controlled flame retardant layer;

[0076] A conductive copper layer was deposited on the surface of the temperature-controlled flame-retardant layer using a magnetron sputtering device to obtain a phase-change temperature-controlled flame-retardant current collector. The time for each deposition was 150 s, and the thickness of the copper layer was 1 μm after 50 depositions.

[0077] Example 5

[0078] The phase-change temperature-controlled flame-retardant current collector provided in this embodiment is prepared by the following steps:

[0079] A 10cm*10cm*20μm QAl10-4-4 aluminum bronze foil (the mass fractions of copper, aluminum, iron, and nickel are 78%, 11.0%, 5.5%, and 5.5%, respectively) was placed in a 1L acidic aqueous solution for chemical corrosion treatment. The ratio of the acidic aqueous solution was 1.0MH2SO4+1.0M HCl+1.0M H3PO4, and the reaction was carried out at 60°C and 600rpm for 24h. After the reaction was completed, it was washed with deionized water and anhydrous ethanol three times each, and the porous copper film was obtained after drying.

[0080] The porous copper film treated initially was used as the anode, and an electrolytic cell was formed with a phosphor copper sheet cathode and an aqueous electrolyte to perform electrolytic corrosion treatment on the porous copper film. The ratio of the aqueous electrolyte was 0.5M CuSO4+1.5MH2SO4, and the current density of the electrochemical corrosion was 2.0mA / cm 2 , the corrosion time is 3h. After completion, it is washed with deionized water and anhydrous ethanol three times respectively, and the secondary treated porous copper film is obtained after drying;

[0081] Tetracosane and trimethyl phosphate and triphenyl phosphate (wherein the mass ratio of trimethyl phosphate to triphenyl phosphate is 2:3) in a mass ratio of 95:5 are stirred at 300 rpm for 2 hours at 60°C, and the secondary treated porous copper film is immersed in the molten mixture and placed at 60°C and a vacuum degree of -0.8MPa for 5 minutes. The porous copper film filled with phase change material and flame retardant is taken out, placed in two polyethylene filter membranes, and hot pressed to remove the residual liquid on the surface. The hot pressing conditions are a pressure of 0.2MPa, a temperature of 55°C, and a duration of 5 minutes. After completion, it is cooled at room temperature to obtain a temperature-controlled flame retardant layer;

[0082] The phase-change temperature-controlled flame-retardant current collector is obtained by depositing an aluminum layer using evaporation coating, and the thickness of the aluminum layer is 1.5 μm.

[0083] Example 6

[0084] The phase-change temperature-controlled flame-retardant current collector provided in this embodiment is prepared by the following steps:

[0085] A 10cm*10cm*20μm QMn12-8-3-2 manganese copper foil (the mass fractions of copper, manganese, aluminum, iron, and nickel are 71%, 14.0%, 8.5%, 4%, and 2.5%, respectively) was placed in a 1L acidic aqueous solution for chemical corrosion treatment. The ratio of the acidic aqueous solution was 1.0M H2SO4+1.0M CH3COOH+1.0M H3PO4. The reaction was carried out at 50°C and 400rpm for 24h. After the reaction was completed, it was washed with deionized water and anhydrous ethanol three times each, and the porous copper film was obtained after drying.

[0086] The porous copper film treated initially was used as the anode, and an electrolytic cell was formed with a phosphor copper sheet cathode and an aqueous electrolyte to perform electrolytic corrosion treatment on the porous copper film. The ratio of the aqueous electrolyte was 0.5M CuSO4+1.5MH2SO4, and the current density of the electrochemical corrosion was 0.5mA / cm 2 , the corrosion time is 6h. After completion, it is washed with deionized water and anhydrous ethanol three times respectively, and the secondary treated porous copper film is obtained after drying;

[0087] Hexadecanol and trimethyl phosphate and triethyl phosphate (wherein the mass ratio of trimethyl phosphate to triethyl phosphate is 4:1) in a mass ratio of 90:10 are stirred at 400 rpm for 2 hours at 60°C, and the secondary treated porous copper film is immersed in the molten mixture and placed at 50°C and a vacuum degree of -0.6MPa for 20 minutes. The porous copper film filled with phase change material and flame retardant is taken out, placed in two polyethylene filter membranes, and hot pressed to remove residual liquid on the surface. The hot pressing conditions are a pressure of 0.02MPa, a temperature of 80°C, and a duration of 1min. After completion, it is cooled at room temperature to obtain a temperature-controlled flame retardant layer;

[0088] The phase change temperature controlled flame retardant current collector is obtained by chemical copper plating, and the thickness of the copper layer is 3 μm.

[0089] Example 7

[0090] The phase-change temperature-controlled flame-retardant current collector provided in this embodiment is prepared by the following steps:

[0091] A 10cm*10cm*30μm B45 white copper foil (the mass fractions of copper and nickel are 55% and 45% respectively) was placed in 1L of acidic aqueous solution for chemical corrosion treatment. The ratio of the acidic aqueous solution was 1.0MH2SO4+1.0M H3PO4. The reaction was carried out at 80℃ and 200rpm for 48h. After the reaction was completed, it was washed with deionized water and anhydrous ethanol three times each, and the porous copper film was obtained after drying.

[0092] The porous copper film treated initially was used as the anode, and an electrolytic cell was formed with a phosphor copper sheet cathode and an aqueous electrolyte to perform electrolytic corrosion treatment on the porous copper film. The ratio of the aqueous electrolyte was 0.5M CuSO4+1.0MH2SO4, and the current density of the electrochemical corrosion was 1.0mA / cm 2 , the corrosion time is 3h. After completion, it is washed with deionized water and anhydrous ethanol three times respectively, and the secondary treated porous copper film is obtained after drying;

[0093] Stearic acid and trimethyl phosphate, triethyl phosphate, and triphenyl phosphate in a mass ratio of 95:5 (wherein the mass ratio of trimethyl phosphate, triethyl phosphate to triphenyl phosphate is 2:2:1) are stirred at 85°C and 400 rpm for 1 hour, and the secondary treated porous copper film is immersed in the molten mixture and placed at 50°C and a vacuum degree of -0.8MPa for 10 minutes. The porous copper film filled with phase change material and flame retardant is taken out, placed in two polyethylene filter membranes, and hot pressed to remove residual liquid on the surface. The hot pressing conditions are a pressure of 0.2MPa, a temperature of 60°C, and a duration of 4min. After completion, it is cooled at room temperature to obtain a temperature-controlled flame retardant layer;

[0094] The temperature-controlled flame-retardant layer is used as the cathode, and the phosphor copper sheet anode and commercial copper plating solution form an electrolytic cell to perform surface electroplating on the flame-retardant phase-change composite film. The current density of the surface electroplating treatment is 2.0 mA / cm 2 The duration is 1h, and the thickness of the electroplated layer is 2μm. After completion, it is washed three times with deionized water and anhydrous ethanol, and dried to obtain a phase change temperature controlled flame retardant current collector.

[0095] Comparative Example 1

[0096] The difference from Example 1 is that step S1 is missing.

[0097] During the experiment, the inventors found that: after the step S1 is missing, Figure 4 As shown, the porous copper foil prepared in step S2 has large pore size (>2 μm) and uneven distribution, and has weak adsorption force on the mixture of phase change material and flame retardant, and cannot effectively encapsulate it in the pores.

[0098] Comparative Example 2

[0099] The difference from Example 2 is that in step S2, the current density is 4 mA / cm 2 .

[0100] During the experiment, the inventor found that: Figure 5 As shown, a large electrochemical corrosion current will cause the porous copper foil to produce an oversized (>5 μm) and discontinuous pore structure. The porous copper foil is brittle and easily broken, and steps S3 and S4 cannot be performed.

[0101] Comparative Example 3

[0102] The difference from Example 3 is that in step S3, the mass ratio of the phase change material to the flame retardant is 60:40.

[0103] During the experiment, the inventors found that when the mass proportion of the flame retardant is too high, the mixture of the phase change material and the flame retardant cannot be cured at room temperature, so it is easy to leak in step S4 and contaminate the surface, resulting in failure to deposit the conductive coating.

[0104] Comparative Example 4

[0105] The difference from Example 4 is that in step S3, the mass ratio of phase change material to flame retardant is 99:1.

[0106] During the experiment, the inventors found that when the mass ratio of the flame retardant is too low, the flame retardant effect is poor and it cannot be released quickly when the battery thermally runs away, causing the battery to overheat and catch fire quickly.

[0107] Comparative Example 5

[0108] The difference from Example 5 is that the porous copper film adsorbed with the phase change material and the flame retardant is not subjected to hot pressing treatment.

[0109] During the experiment, the inventors found that if the solidified phase change material and flame retardant remaining on the surface of the porous copper foil film are not removed by hot pressing, the conductive coating deposition in step S4 will fail.

[0110] Comparative Example 6

[0111] The difference from Example 6 is that commercial copper foam (the material is purchased from Sanhe New Material Technology Co., Ltd.) is used to replace the porous copper film.

[0112] During the experiment, the inventors found that the commercial copper foam available on the market has a pore size of more than 150 μm, has a weak adsorption effect on the mixture of phase change material and flame retardant, has a poor filling effect, and is extremely prone to leakage.

[0113] Performance Test:

[0114] The above-mentioned embodiments 1 to 7 were subjected to the following performance tests, including:

[0115] Thermal conductivity test: ISO22007-2 "Plastics. Determination of thermal conductivity and thermal diffusivity. Part 2: Instantaneous planar heat source (heating plate) method" (this standard is applicable to thermal conductivity in the range of 0.01 to 500 W / m·K) is used to test the thermal conductivity of the phase change temperature-controlled flame-retardant current collector described in each embodiment.

[0116] Phase change temperature and phase change enthalpy test: The phase change temperature and phase change latent heat value of the phase change temperature-controlled flame-retardant current collector described in each embodiment were tested by differential scanning calorimetry (DSC).

[0117] Referring to the above test standards, the phase change materials obtained in the examples and comparative examples were tested, and the test results are shown in Table 1 below:

[0118] Table 1 Thermal performance test results

[0119]

[0120] It can be seen from the thermal performance test results in Table 1 that due to the high thermal conductivity and high electrical conductivity of the deposited metal layer and the porous copper film, the phase-change temperature-controlled flame-retardant current collector obtained in the embodiment has good thermal conductivity and electrical conductivity at the same time to meet the requirements of rapid heat absorption and normal operation of the battery. The thermal conductivity coefficient of the phase-change temperature-controlled flame-retardant current collector obtained in the embodiment exceeds 150W / m·K, and its thermal conductivity is improved by three orders of magnitude compared with the paraffin phase change material (0.2W / m·K) used, which is also higher than most existing phase change composite materials. In addition, its volume specific latent heat exceeds 100J / cm 3 Compared with the paraffin phase change material (168J / cm 3 ), the volume utilization rate of the filled paraffin is very high, so it has a high practical application value. At the same time, the phase change temperature of the phase change temperature controlled flame retardant current collector obtained in Example 1 is 42.6°C. Considering that the suitable operating temperature of commercial lithium-ion batteries is 25-45°C, the phase change temperature controlled flame retardant current collector is very suitable for temperature control inside the battery.

[0121] Taking Example 1 as an example, Example 1 and commercial copper foil (material purchased from Kruder Technology Co., Ltd.) were assembled into 0.5Ah lithium iron phosphate / graphite soft-pack batteries. The other components of the battery (positive electrode current collector, positive electrode, negative electrode, separator, electrolyte) were consistent, and the battery was tested for the following performance:

[0122] (1) Cycle capacity retention rate

[0123] (2) Temperature rise of fully charged battery after 3C discharge

[0124] (3) Maximum temperature of thermal runaway

[0125] The test results are recorded in Table 2 below.

[0126] Table 2 Battery performance and thermal safety

[0127]

[0128] According to the results in Table 2, the 0.5Ah lithium iron phosphate / graphite soft pack battery assembled with the phase change temperature controlled flame retardant current collector has good cycle performance, with a capacity retention rate of 94.9% after 100 cycles at 25°C and a capacity retention rate of 82.9% after 100 cycles at 55°C, which is basically equivalent to commercial copper foil. The stable cycle at 55°C proves the good encapsulation of phase change materials and flame retardants. The fully charged battery (SOC = 100%) was discharged at a 3C rate. After the discharge, the temperature rise of the battery using the phase change temperature controlled flame retardant current collector was only 10.2°C, which was 9.3°C lower than that of the commercial copper foil. In addition, the thermal abuse of the battery caused thermal runaway, and the release of the flame retardant made the maximum temperature of the battery only 181.4°C, which was much lower than the 486.2°C of the commercial copper foil. Therefore, the phase change temperature controlled flame retardant current collector effectively improved the thermal stability of the battery and suppressed thermal runaway.

[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A phase-change temperature-controlled flame-retardant current collector, comprising a conductive coating (1) and a temperature-controlled flame-retardant layer (2), wherein the conductive coating comprises a first conductive coating (11) and a second conductive coating (12), characterized in that: The conductive coating (1) is used to load active materials and encapsulate the temperature-controlling flame-retardant layer (2), and the temperature-controlling flame-retardant layer (2) is arranged between the first conductive coating (11) and the second conductive coating (12); The temperature-controlling flame-retardant layer (2) is based on a porous copper film, and the porous copper film is filled with a phase change material and a flame retardant.

2. The phase-change temperature-controlled flame-retardant current collector according to claim 1, characterized in that: The material of the first conductive coating (11) and / or the second conductive coating (12) is selected from one of aluminum, copper, silver, nickel or platinum; the thickness of any of the conductive coatings is 1 to 5 μm.

3. The phase-change temperature-controlled flame-retardant current collector according to claim 1, characterized in that: The temperature-controlling flame-retardant layer (2) has a thickness of 10 to 50 μm.

4. The phase-change temperature-controlled flame-retardant current collector according to claim 3, characterized in that: The porous copper film has a porosity of 40-80%, an average pore size of 0.5-2.0 μm, and a thickness of 10-50 μm; The phase change material is selected from one or more of paraffin, n-docosane, tetracosane, tetradecanol, hexadecanol, octadecyl alcohol, lauric acid, myristic acid, hexadecanoic acid and stearic acid; The flame retardant is selected from one or more of trimethyl phosphate, triethyl phosphate and triphenyl phosphate.

5. The phase-change temperature-controlled flame-retardant current collector according to claim 4, characterized in that: The mass ratio of the phase change material to the flame retardant is 80:20 to 97:

3.

6. A method for preparing the phase-change temperature-controlled flame-retardant current collector according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: S1: Pre-preparation of porous copper film: placing a copper alloy foil in an acidic aqueous solution, heating and stirring, taking out the copper alloy foil after no bubbles are generated on the surface, washing it, and drying it to obtain a pre-treated porous copper film; S2: adjusting the pores of the porous copper film: using the porous copper film in step S1 as an anode, the phosphor copper sheet as a cathode, and a mixed aqueous solution of sulfuric acid and copper sulfate as an electrolyte, connecting a constant current power supply to electrochemically corrode the porous copper film; after the treatment is completed, washing and drying to obtain a secondary treated porous copper film; S3: Preparation of temperature-controlled flame-retardant layer (2): heating and stirring the phase change material and the flame retardant to form a liquid mixture; immersing the porous copper foil in step S2 in the liquid mixture and placing it in a constant temperature vacuum environment to obtain a porous copper film adsorbed with the phase change material and the flame retardant, placing it between polyethylene filter membranes, hot pressing, and cooling it at room temperature to obtain the temperature-controlled flame-retardant layer (2); S4: Preparation of a phase-change temperature-controlled flame-retardant current collector: depositing a conductive coating (1) on both sides of the temperature-controlled flame-retardant layer (2) in step S3 to prepare a phase-change temperature-controlled flame-retardant current collector; The deposition method is selected from one of evaporation coating, magnetron sputtering, electroplating or chemical plating.

7. The method according to claim 6, characterized in that In step S1, the copper alloy is selected from one of copper-zinc alloy, copper-nickel alloy, copper-zinc-nickel alloy, copper-tin alloy or copper-manganese alloy; in the copper alloy, the mass fraction of copper is 30-80%; The thickness of the foil is 10 to 50 μm; The acid used in the acidic aqueous solution is selected from one or more of sulfuric acid, hydrochloric acid, phosphoric acid and acetic acid, and the concentration is 0.1-1.0 mol / L; The heating and stirring temperature is 50-90° C., and the stirring speed is 200-600 rpm.

8. The method according to claim 6, characterized in that In step S2, in the electrolyte, the concentration of sulfuric acid is 0.1-2.0 mol / L, and the concentration of copper sulfate is 0.1-0.6 mol / L; The conditions of the electrochemical corrosion treatment are: the current density is 0.5-2.0 mA / cm 2 , the corrosion time is 0.5 to 6 hours.

9. The method according to claim 6, characterized in that In step S3, the heating and stirring temperature is 40-90°C, the stirring speed is 200-600 rpm, and the duration is 0.5-4h; The constant temperature vacuum conditions are: vacuum degree -0.6 to -0.8 MPa, temperature 50 to 80°C, and duration 3 to 20 minutes; The hot pressing conditions are: pressure 0.02-0.5 MPa, temperature 50-90° C., and duration 1-5 min.

10. Use of the phase-change temperature-controlled flame-retardant current collector according to any one of claims 1 to 5 in a lithium battery.

Citation Information

Patent Citations

  • Phase-change temperature-adjusting diaphragm as well as preparation method and application thereof

    CN112928389A

  • Lithium ion battery

    CN113823850A

  • Composite current collector and preparation method thereof

    CN116344832A

  • Current collector and preparation method thereof, electrode plate, battery and electric device

    CN117894996A

  • Current collector for a battery cell

    DE102021211598A1

Cited By

  • Composite current collector, pole piece, dual-ion battery and preparation method

    CN120473507A

  • Phase change composite current collector and preparation method and application thereof

    CN120511307A